2008
DOI: 10.1039/b806421k
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of required monitoring time for obtaining validation data in enclosed spaces

Abstract: Methods for estimating airborne contaminant concentrations at specific locations within enclosed spaces, such as mathematical models and computational fluid dynamics (CFD), often are validated against directly measured concentrations. However, concentration variation with time introduces uncertainty into the measured concentration. Failure to determine monitoring time requirements can lead to errors in quantifying representative concentrations, which are likely to be attributed to errors in the method being va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…An inadequate choice may result in large uncertainties or even in wrong information, potentially leading to incorrect conclusions. 16 This problem is associated with the temporal variability of indoor T, RH and contaminant concentration. Their variation is caused by the inuence of numerous factors on indoor air.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An inadequate choice may result in large uncertainties or even in wrong information, potentially leading to incorrect conclusions. 16 This problem is associated with the temporal variability of indoor T, RH and contaminant concentration. Their variation is caused by the inuence of numerous factors on indoor air.…”
Section: Introductionmentioning
confidence: 99%
“…Our work contributes to the development of the relevant methodology. 16,21 The objective of this work is to determine whether the long-term monitoring session can be represented by a shorter measurement period. We proposed to apply scaled relative entropy as a measure which may be used to evaluate the representativeness of dataset in indoor air monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…The 15 second averaging period was long enough to allow a resting wearer several complete breaths.'' Yet, data from Lee et al 5 found that the magnitude of exposure concentration indoors may change an average of 15% within 4 s with a standard deviation (SD) of 20% (n ¼ 284) even when source concentration was held constant. Hart 4 performed rigorous experiments and determined that the pumps she used stabilized to new speeds in about 1 s (page 128).…”
Section: Prior Workmentioning
confidence: 99%
“…Assessing worker exposures to airborne hazards is an essential element of industrial hygiene practice. Personal exposures must be known in order to (1) determine compliance with exposure limits set by various regulatory agencies, (2) specify personal protective equipment to be worn to isolate workers from hazards, (3) tailor the design of control systems for work sites and to measure the effectiveness of these controls, (4) develop databases for epidemiological dose-response studies, and (5) project the risks of contracting diseases from exposures. Collecting samples representative of exposures is the foundation underlying valid assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, it is transient most of the time. Because of these circumstances, valuable knowledge of the environmental parameters should be based on series of measurements performed in the time domain in properly selected locations [5,6].…”
Section: Introductionmentioning
confidence: 99%